2021
DOI: 10.3892/mmr.2021.12141
|View full text |Cite
|
Sign up to set email alerts
|

Silencing a disintegrin and metalloproteinase‑33 attenuates the proliferation of vascular smooth muscle cells via PI3K/AKT pathway: Implications in the pathogenesis of airway vascular remodeling

Abstract: Accumulating evidence suggests that pulmonary expression of a disintegrin and metalloproteinase-33 (ADAM33) serves a key role in the pathogenesis of airway remodeling-related diseases, including asthma. Airway vascular proliferation has been recognized as a key feature of airway remodeling. Our previous study showed that ADAM33 is constitutively expressed in airway vascular smooth muscle cells in patients with asthma, suggesting a potential role of ADAM33 in regulating airway vascular remodeling. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…For example, the expression of a disintegrin and metalloproteinase-33 (ADAM33), which belongs to the ADAM metalloproteinase family, is associated with airway inflammation, hypersensitivity and remodeling in asthmatic patients. Moreover, the silencing of this gene led to proliferation inhibition and induced the apoptosis of human aortic smooth muscle cells [ 10 ]. Matrix metalloproteinases (MMPs) are important in extracellular matrix degradation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the expression of a disintegrin and metalloproteinase-33 (ADAM33), which belongs to the ADAM metalloproteinase family, is associated with airway inflammation, hypersensitivity and remodeling in asthmatic patients. Moreover, the silencing of this gene led to proliferation inhibition and induced the apoptosis of human aortic smooth muscle cells [ 10 ]. Matrix metalloproteinases (MMPs) are important in extracellular matrix degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous data showed that the silencing of the ADAM33 gene inhibited the cell cycle transition of HASMCs from the G0/G1 phase to the S phase, prolonged cell cycle progression, and suppressed cell proliferation [ 11 ]. To clarify the mechanism by which ADAM33 silencing regulated the cell cycle transition of HASMCs, we examined the expression levels of the downstream factors of the PI3K/AKT/mTOR pathway (the transcription factor FOXO1 and the cell cycle regulator cyclin D1) in HASMCs.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed that a lentiviral vector carrying shRNA targeting ADAM33 (LV-ADAM33) effectively silenced the ADAM33 gene in HASMCs [ 11 ]. In this study, HASMCs were transfected with LV-ADAM33 (MOI = 10, 1 × 10 7 TU/mL; the LV-ADAM33 group) or a negative control vector (MOI = 10, 1 × 10 7 TU/mL; the LV-NC group) for 72 h using the HitransG P reagent (cat no.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations